2019
DOI: 10.1037/edu0000284
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial for some or for everyone? Exploring the effects of an autonomy-supportive intervention in the real-life classroom.

Abstract: The present study investigated whether an autonomy-supportive intervention influenced students’ need satisfaction, achievement emotions, and strategies of self-regulated learning differently depending on several student characteristics. The study was conducted with a sample of 345 9th-grade students in 17 physics classrooms who were randomly assigned to an experimental or a control condition. In both conditions, their physics teachers taught a standardized teaching unit on heat transfer that either entailed au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 74 publications
2
26
0
1
Order By: Relevance
“…Marsh et al (2019), for example, note that competency self‐beliefs are “central in theoretical models of motivation” (p. 332). Similarly, Flunger, Mayer, and Umbach (2019) found that an autonomy‐supportive teaching style (e.g., offering students choices and providing rationales for tasks) was linked to better need satisfaction, self‐regulated learning, and positive emotions about achievement among ninth grade German physics students. Tessier, Sarrazin, and Ntoumanis (2010) showed that a teacher training explicitly based on self‐determination theory could improve teachers’ autonomy support, structure, and interpersonal involvement with students, with resulting improvement in students’ psychological need satisfaction and self‐reported class engagement.…”
Section: Introductionmentioning
confidence: 90%
“…Marsh et al (2019), for example, note that competency self‐beliefs are “central in theoretical models of motivation” (p. 332). Similarly, Flunger, Mayer, and Umbach (2019) found that an autonomy‐supportive teaching style (e.g., offering students choices and providing rationales for tasks) was linked to better need satisfaction, self‐regulated learning, and positive emotions about achievement among ninth grade German physics students. Tessier, Sarrazin, and Ntoumanis (2010) showed that a teacher training explicitly based on self‐determination theory could improve teachers’ autonomy support, structure, and interpersonal involvement with students, with resulting improvement in students’ psychological need satisfaction and self‐reported class engagement.…”
Section: Introductionmentioning
confidence: 90%
“…To illustrate, Wörtler et al (2020) found in samples of both Dutch and American employees that experiences of volition, mastery, and connection at work are conducive to employees' engagement and organizational citizenship behavior, with need strength moderating these effects only to a very limited degree. Similarly, experimental studies indicate that learners benefit from an autonomy-supportive teaching style, with participants' motivational differences affecting these effects only to a limited extent (e.g., Delrue et al 2019b;De Meyer et al 2016;Flünger et al 2019).…”
Section: Advancementsmentioning
confidence: 99%
“…Presumably, the functional significance of the reward was different for autonomy‐, relative to control‐oriented individuals (see also Hagger, Koch, & Chatsizarantis, ). Other studies have focused on individual differences in students’ motivational orientations, showing that even controlled individuals suffer from exposure to controlling teaching (De Meyer et al, ), whereas autonomy‐oriented learners can derive greater benefits from a need‐supportive class (Flünger, Mayer, & Umbach, ; Mouratidis, Vansteenkiste, Sideridis, & Lens, ).…”
Section: Relations Between Sdt and Wttmentioning
confidence: 99%